Organizacja pracy w firmie Стрийський вагоноремонтний завод (SVZ) - Bayramova, Yaryna (My University, 2013)
Organizacja pracy - to jeden z najważniejszych etapów formułowania działania firmy. Organizacja jest kluczem do sukcesu i efektywności pracowników. Efektywność wykonywanej pracy zależy od dobrego rozporządzenia czasem. Nawet mały błąd w organizacji pracy, może spowodować zmniejszenie efektywności pracy. W procesie organizacji pracy trzeba brać pod uwagę jak największą liczbę czynników, w związku z tym ważna jest umiejętność ich identyfikowania, w prezentowanej pracy posłużyły do tego studia literaturowe z zakresu teorii organizacji.

The organization of work - this is one of the most important stages of the formulation of the company. Organization is the key to the success and efficiency of employees The effectiveness of the work depends on good time regulation. Even a small blend in work organization can reduce productivity. In the process of organization of work you have to take into account many factors, therefore, important to be able to identify them, in the present study were used to study the literature on the theory of organization.
The organization of work in the company Стрийський вагоноремонтний завод (SVZ)
Keywords: organizacja; organizacja pracy; systemy organizacji; analiza organizacji pracy w firmie; organization; organization of work; systems of organization; analysis of the organization of work in the company; organizational structures; struktury organizacyjne